Thermally Induced Mode Amplification Characteristics of Large Mode Area Segmented Cladding Fiber - Caijian Xie; Tigang Ning; Jingjing Zheng; Jing Li; Xiaowei Dong; Yanbiao Chang; Li Pei (IEEE Photonics Journal)
A model of amplifier based on large mode area (LMA) segmented cladding fiber (SCF) is proposed. High order modes (HOMs) filtering effect and thermal-induced modal evolution characteristics are theoretically investigated by the few-mode steady state rate equations and heat conduction equation. Simulation results show that an amplifier based on ytterbium doped SCF presents much better HOMs suppression and mode beam quality than the amplifier based on conventional step-index fiber when achieving single-mode operation by coiling fiber. Furthermore, heat load generating in the core of ytterbium doped SCF can change the pre-designed refractive index profile through the thermo-optic effect, which induces evolution of mode amplification characteristics, including mode loss decreasing and mode area shrinking. And the co-pumping amplifier ytterbium doped SCF is more advantageous to get large mode area of fundamental mode at the output end, while single-mode operation is achieved much more effectively in the counter-pumping amplifier. These results can provide guidance in the design of high-power single-mode fiber amplifier based on rare-earth doped LMA-SCF.